Auditory Display in Nondestructive Testing of Concrete - Valenzuela, Mark L; Sansalone, Mary J; Krumhansl, Carol L (ACI materials journal, 2006)
Impact-echo is a method for the nondestructive evaluation of concrete or masonry structures that uses transient stress waves generated by short-duration mechanical impact. The research described in this paper addresses the need for engineers to perform rapid yet accurate interpretation of impact-echo signals during testing of large plate structures that require evaluation at hundreds or thousands of points, such as bridge decks, walls, and slabs. This paper describes the development of an auditory display system to present impact-echo spectra as computer-synthesized sound to field engineers in real-time. This system is meant to provide an easy-to-use and efficient aid to alert field engineers to the presence of flaws in plate structures, but it does not replace the well-established quantitative interpretation of signals to determine the precise location of these flaws. The auditory display system has been evaluated using psychological experiments to examine the learnability and transfer of learning using three groups of 14 subjects each. Results indicate that the auditory displays are learnable and that this learning is transferable to a real scenario. More importantly, the results suggest an efficient two-stage method for pattern recognition training. [PUBLICATION ABSTRACT]